Evaluating an English department: the use of illuminative evaluation procedures in descriptive and diagnostic analysis of English teaching programmes in high schools - Thorpe, Robert Nicholas (Rhodes University, Faculty of Education, Department of Education, 1991)
To evaluate what is actually happening within a High School subject curriculum, the annual parade of marks, percentages and symbol distributions is not by itself adequate, especially in assessing progress towards such English syllabus goals as: That pupils expand their experience of life, gain empathetic understanding of people and develop moral awareness. (3.1. 4 HG) How too, from examination results alone, can a subject head of English assess the success of his objective "to woo his pupils into the reading habit"? (School 1: Goals 1988) Decisions on English department policy and procedures are frequently based on personal hunches and examination results. Few subject departments engage in proper evaluations of their curricula to support decisions made, or to impart meaning upon the countless daily transactions between child and adult, individual and institution in the learning process. This study demonstrates the efficacy of "illuminative evaluation" techniques in opening out an educational innovation (1986 First Language English syllabi of the Cape Education Department) at two High Schools for comment and appraisal. The array of information gathered should be useful in planning and implementing further curricula initiatives. The inherent flexibility of illuminative evaluation procedures and their freedom from large-scale data base requirements needed for 'scientific' models of evaluation are advantageous in investigating the untidy complexities of English teaching. Both 'closed' and 'open' response questionnaires, interviews, and perusal of relevant documents informed the researcher of the views of pupils, parents, English teachers, other subject heads, the two school principals and the education authorities on what waS and ought to be happening in English classes. From the considerable array of information generated, the distress of conscientious English teachers facing unreasonable work-loads emerged clearly. Such teachers are likely to occupy key roles in the non-racial state schools of the future and cannot be regarded as expendable. 'Open schools' present new challenges to existing curricula and the position of English may prove to be critical. Thus it is submitted that English subject heads should be concerned with evaluating their departments so that informed decisions can be taken on future directions. Illuminative evaluation is demonstrably useful in such analyses.
Keywords: English language -- Study and teaching (Secondary) -- South Africa; English language -- Study and teaching (Secondary) -- Evaluation